Enhancing methyldopa solubility via green supercritical fluid techniques using ethanol co-solvent - Hadil Faris Alotaibi; Suleiman Ibrahim Mohammad; Asokan Vasudevan; Suranjana V. Mayani; Suhas Ballal; Munthar Kadhim Abosaoda; Abhayveer Singh; Subhashree Ray; Atreyi Pramanik (Scientific Reports)
Abstract The aim of this study is to investigate the solubility of methyldopa in supercritical carbon dioxide. Solubility was examined at temperatures of 338, 328, 318, and 308 K, in both the presence and absence of a co-solvent. Specifically, ethanol was evaluated as a co-solvent. Semi-empirical and empirical approaches, as well as the Peng-Robinson equation, were applied to analyze the experimental data. The mole fraction (solubility) of methyldopa was found to range from 0.078 × 10−4 (0.21 g/l) to 1.082 × 10−4 (3.38 g/l) in the binary system and from 0.405 × 10−4 (1.38 g/l) to 3.143 × 10−4 (11.33 g/l) as well as from 1.225 × 10−4 (4.60 g/l) to 8.979 × 10−4 (34.94 g/l) at 1 and 3 mol % respectively. The findings indicated that incorporating a co-solvent, particularly ethanol, resulted in a substantial enhancement in solubility. The maximum enhancement was recorded in the methyldopa-ethanol-CO2 system at 12 MPa and 338 K, where the solubility was found to be 15.70 times higher than in pure supercritical carbon dioxide. The models employed for data evaluation exhibited robust correlations with the experimental outcomes. Among these models, the Soltani-Mazloumi model exhibited the strongest correlation with the experimental solubility data.